Penerapan Model Pembelajaran Contextual Teaching And Learning Untuk Meningkatkan Aktivitas Dan Hasil Belajar Administrasi Pajak Di SMKN 1 Sidikalang - Lingga, Marni; Thohiri, Roza; Zainal, Andri; Ramdhansyah (Universitas Tidar, 2024)
This study overcomes the problem of low activity and learning outcomes of students in class XI AKL 1 SMK N 1 Sidikalang, consisting of 36 students. This study aims to improve activity and learning outcomes by using the Contextual Teaching and Learning model. Data were collected through activity observation sheets and learning outcomes tests, then analyzed quantitatively and qualitatively. 1) In cycle I, the first meeting showed an average of 27.77% active activities, then in cycle II, it increased with an average of 77.77% active activities. 2) The average pre-test score was 72.77% with 17 students (47.22%) complete, post-test cycle I 75% with 19 students (52.77%) complete, and post-test cycle II 85.27% with 32 students (88.88%) complete, meeting the success indicator ≥85%. In conclusion, the application of the Contextual Teaching and Learning model succeeded in improving student learning activities and outcomes.